Finite element modelling of bahareque walls under lateral cyclic loading - Garcia-Troncoso, Natividad; Molina-Cedeño, Juan; Vergara-Pin, Miguel; Zambrano-Montalvan, Hilda; Tello-Ayala, Ken; Bompa, Dan V. (Frontiers in Built Environment, 2026)
This study presents a numerical representation of the cyclic behavior and energy dissipation characteristics of cemented bahareque walls using the non-linear modeling procedures. A numerical model was calibrated through experimental tests to fit the nonlinear response, including the stiffness degradation and hysteretic behavior of bahareque walls subjected to reversed cyclic loading. An additional sensitivity analysis was carried out to evaluate the influence of aspect ratio, fastener spacing, frame cross-section, mortar panel thickness, and vertical load on the structural response of the cemented bahareque walls. Results indicate that the calibrated model successfully replicates the energy dissipation capacity of the experimental walls with a relative energy error of 4.84%, despite some localized discrepancies in force predictions. The sensitivity analysis indicated significant variation in hysteretic response associated with fastener spacing, stiffness degradation parameters, and pinching effects. This study also shows that variations in parameters as fastener spacing can affect the model’s lateral loading capacity by up to 23.40%. These results underscore the influence of key modeling parameters on wall structural behavior. The findings demonstrate the suitability of the calibrated numerical model for predicting global seismic demands and highlight critical parameters that influence the cyclic performance and resilience of bahareque walls for affordable housing.